2014
DOI: 10.3945/an.113.005553
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sustainable Diets: A Descriptive Analysis of the Determinants and Processes That Influence Diets and Their Impact on Health, Food Security, and Environmental Sustainability

Abstract: The confluence of population, economic development, and environmental pressures resulting from increased globalization and industrialization reveal an increasingly resource-constrained world in which predictions point to the need to do more with less and in a “better” way. The concept of sustainable diets presents an opportunity to successfully advance commitments to sustainable development and the elimination of poverty, food and nutrition insecurity, and poor health outcomes. This study examines the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
301
0
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(329 citation statements)
references
References 28 publications
(51 reference statements)
4
301
0
24
Order By: Relevance
“…Also, over time, some argue that income may become a weaker determinant of diets, giving thus broader scope for public policy to have a real influence in the future (50) . This deserves to be discussed.…”
Section: Prices and Affordability Of Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, over time, some argue that income may become a weaker determinant of diets, giving thus broader scope for public policy to have a real influence in the future (50) . This deserves to be discussed.…”
Section: Prices and Affordability Of Dietsmentioning
confidence: 99%
“…Trends on dietary patterns towards more healthy items and towards more unhealthy items (see earlier) are not correlated which makes one wonder if it is not because these trends are driven by different policies and incentives, tendencies for increase of unhealthy items being driven by marketing and promotion of more healthy items by government policies (19) . There could also be reluctance from policy makers to propose changes that might have a negative effect on economic sectors (50) . Conversely, too simple messages can have detrimental impacts on nutrition.…”
Section: Consumer Informationmentioning
confidence: 99%
“…Food security, of which nutrient adequacy is an essential condition, is the ultimate objective of a sustainable food system (18) , but only recently have conservation policies begun to incorporate food security objectives (20) . Developing effective policies to support sustainable food systems is hindered by a lack of metrics that are useful in understanding how diets can improve population health while conserving environmental resources (21) . Previous research has demonstrated how the Functional Diversity indicator (22) , developed by ecologists to evaluate the impact of biodiversity in natural and managed systems (23) and to test the resilience of those systems (24) , can be adapted to describe the diversity of nutrients in cropping systems.…”
mentioning
confidence: 99%
“…In recent years, within the international debate on sustainability, food security and nutrition (1,2) , sustainable diets have emerged as a challenging public health nutrition issue (3)(4)(5)(6)(7) as well as a critical issue for sustainable food systems (8)(9)(10) . The incorporation of sustainability aspects into dietary guidelines has been increasingly discussed over the past decades to make diets healthier for consumers as well as for the environment.…”
mentioning
confidence: 99%